A Efektivitas Peran dan Fungsi Tim Kendali Mutu Kendali Biaya (TKMKB) Provinsi Sulawesi Selatan Dalam Memberikan Rekomendasi Penyelesaian Dispute Klaim Tahun 2021: Efektivitas Peran dan Fungsi TKMKB Dalam Memberikan Rekomendasi Penyelesaian Dispute Klaom FKRTL - Muhayyina Wahidah; Irawan Yusuf (BPJS Kesehatan, 2022)
This study aims to assess the effectiveness of the role and function of the South Sulawesi Province Quality and Cost Control Team in providing recommendations for the settlement of disputed claims. The method used is descriptive quantitative by comparing the claim dispute data in the Month of Loading from January to December 2021 in South Sulawesi Province. The data sources used are from the Monthly Routine Reports of Claims for Branch Office disputes as well as data on increasing claim maturity. The results of the study found that there was a decrease in dispute claim cases after the Quality and Cost Control Team Meeting in 6 Branch Offices and an increase in the quality of the maturity of advanced outpatient and advanced hospitalization claims, so that the role and function of Quality and Cost Control Team in providing recommendations for dispute resolution claims to Social Security Agency of Health and hospital was considered effective.